Impact of periprocedural biomarker elevation on mortality in stable angina pectoris patients undergoing elective coronary intervention: a systematic review and meta-analysis including 24 666 patients. Issue 2 (March 2020) - Soud, Mohamad; Hideo-Kajita, Alexandre; Ho, Gavin; Yacob, Omar; Alahdab, Fares; King, Fred; Waksman, Ron; McFadden, Eugène P.; Garcia-Garcia, Hector M.
Abstract : Background: Uncertainty remains regarding the exact prognostic impact of biomarker elevation following percutaneous coronary intervention in patients with stable angina pectoris and the subsequent risk of death. We sought, therefore, to evaluate the effect of periprocedural myocardial infarction on the subsequent mortality risk following percutaneous coronary intervention in patients with stable angina pectoris and normal preprocedural cardiac biomarkers level. Methods: After a systematic literature search was done in PubMed and EMBASE, we performed a meta-analysis of studies with post-procedural cardiac biomarkers data. All-cause mortality and cardiac death were evaluated in subjects with stable angina pectoris who underwent an elective coronary intervention. Results: Fourteen studies with 24 666 patients were included. The mean age was 64.2 years ± 9.8 with about 3-quarters (74.9%) of these patients being men. The mean duration of follow-up was 18.1 months ± 14.3. Periprocedural myocardial infarction, based on study-specific biomarker criteria, occurred in 14.3% of the patients. Periprocedural myocardial infarction conferred a statistically significant increase in the risk of all-cause mortality (odds ratio, 1.62; 95% confidence interval, 1.30–2.01; P < 0.0001; I 2 = 0%); where reported separately, cardiac death was also significantly increase (odds ratio, 2.77; 95% confidence interval, 1.60–4.80; P = 0.0003; I 2 = 0%). Conclusion: The occurrence of periprocedural myocardial infarction after an elective percutaneous coronary intervention in patients with stable angina pectoris is associated with a statistically significant increase in subsequent all-cause mortality and cardiac mortality. Abstract : Supplemental Digital Content is available in the text.